2011
DOI: 10.1097/coh.0b013e3283473405
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antiretroviral therapy on liver disease

Abstract: Current expert guidelines recommend earlier treatment of HIV infection in persons coinfected with hepatitis B virus and possibly hepatitis C virus. It is unknown whether an earlier start of ART is beneficial for the liver in HIV-monoinfected patients. Future research should focus on long-term ART-related hepatotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…[7][8][9][10]20 It is unlikely that a greater exposure to these drugs could explain the lower risk of MI in those with high ALT levels for 2 reasons. First, if this were to explain our findings, the drugs that are most likely to cause ALT elevations would also have to be associated with a reduced MI risk; the only antiretroviral drug where this might plausibly be the case is nevirapine, which is associated with a more favorable lipid profile.…”
Section: Discussionmentioning
confidence: 98%
“…[7][8][9][10]20 It is unlikely that a greater exposure to these drugs could explain the lower risk of MI in those with high ALT levels for 2 reasons. First, if this were to explain our findings, the drugs that are most likely to cause ALT elevations would also have to be associated with a reduced MI risk; the only antiretroviral drug where this might plausibly be the case is nevirapine, which is associated with a more favorable lipid profile.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have demonstrated that HIV patients treated with highly active antiretroviral therapy have a greater risk of venous thromboembolism events, compared to age-matched control. 21 Thus, we also assessed the risk of PVT in the subgroup of IPH patients without HIV infection. Interestingly, VB at diagnosis of IPH remained as an independent predictive factor of PVT in non-HIV IPH patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the less severe form, namely minor neurocognitive motor disorder (MCMD), remains to be a significant problem [39,40]. Despite antiretroviral effects, the use of antiretroviral therapy (ART) drugs has been associated with the development of several adverse events, such as increased cardiovascular risk [41], hepatotoxicity [42], and renal toxicity [43]. Emerging evidence showing activated autophagy, along with the use of ART, suggests that autophagy could be another mechanism that is affected by these classes of drugs.…”
Section: Autophagy and Hiv-1mentioning
confidence: 99%